Landasan Psikologis dalam Pengembangan Kurikulum pada Mata Pelajaran PAI dan Budi Pekerti Sekolah Dasar: The Psychological Foundation in Curriculum Development for Islamic Education and Character Education Subjects in Elementary Schools - Yasmin RF, Firyal (Epistemic: Jurnal Ilmiah Pendidikan, 2022)
The curriculum, as a system consisting of four main components, namely objectives, content, learning activities (teaching process), and evaluation (evaluation component), is an integral part of the education system. Psychology plays a crucial role in the development of school curricula, as it considers psychological aspects in the learning process. This study focuses on the psychological foundation of the Islamic Education curriculum (PAI). The research method used is literature review, which involves collecting data from various sources such as journals, books, and conference proceedings focusing on psychology and education. The development of the PAI curriculum should be responsive to students' development, including the achievement of competencies and the implementation of effective teaching methods. The PAI curriculum should be designed by considering students' psychological needs to provide an effective learning experience. This involves a deep understanding of how students learn and how they engage with learning materials. By considering psychological foundations, the curriculum can be designed to facilitate more effective and relevant learning for students. Additionally, the role of the social environment, family support, and individual motivation are also important factors to be considered in the development of the PAI curriculum to create a conducive learning environment for students. Keywords: Character Education, Islamic Education Curriculum (PAI Curriculum), Islamic Education Subject, Psychology. Abstrak: Kurikulum, sebagai suatu sistem yang terdiri dari empat komponen utama, yakni tujuan, isi (materi/konten), kegiatan pembelajaran (proses pembelajaran), dan evaluasi (komponen evaluasi), merupakan bagian integral dari dunia pendidikan. Psikologi memiliki peran yang krusial dalam pengembangan kurikulum sekolah, karena mempertimbangkan aspek-aspek psikologis dalam proses pembelajaran. Penelitian ini fokus pada landasan psikologis dari kurikulum Pendidikan Agama Islam (PAI). Metode penelitian yang digunakan adalah studi literatur, yang melibatkan pengumpulan data dari berbagai sumber seperti jurnal, buku, dan hasil konferensi yang berfokus pada psikologi dan pendidikan. Penyusunan kurikulum PAI haruslah responsif terhadap perkembangan siswa, termasuk pencapaian kompetensi dan penerapan metode pembelajaran yang efektif. Kurikulum PAI haruslah dirancang dengan memperhatikan kebutuhan psikologis siswa agar dapat memberikan pengalaman belajar yang efektif. Hal ini melibatkan pemahaman yang mendalam tentang bagaimana siswa belajar dan bagaimana mereka menghadapi materi pelajaran. Dengan mempertimbangkan landasan psikologis, kurikulum dapat dirancang untuk memfasilitasi pembelajaran yang lebih efektif dan relevan bagi siswa. Selain itu, peran lingkungan sosial, dukungan keluarga, dan motivasi individu juga merupakan faktor penting yang perlu dipertimbangkan dalam pengembangan kurikulum PAI agar dapat menciptakan lingkungan pembelajaran yang kondusif bagi siswa. Kata Kunci: Budi Pekerti, Kurikulum PAI, Mata Pelajaran PAI, Psikologi.